Aktivitas fisik, stress, dan asupan makanan terhadap tekanan darah pada wanita prediabetes - Syahitdah, Rohmah; Nissa, Choirun (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2018)
Backgrounds: Prediabetes and hypertension was being a health issue in the world. Prediabetes and hypertension that occur together will increase the risk of developing Type 2 Diabetes Mellitus (T2DM) and cardiovascular disease. Risk factor of prediabetes and hypertension who can changed is phyisical activity, stress, and nutrition intake.Objectives: This study aims to determine the association between physical activity and stress with blood pressure in prediabetes woman.Methods: The study was done at Semarang in April-June 2016. The cross-sectional study design with the 28 subjects predibetes woman aged 35-50 years selected by consecutive-sampling method. The data taken were blood presure, fat, fiber, sodium, pottasium, calsium, magneisum intake, physical activity score, and stress score. Spearman test were used to determine the association between physical activity and stress with blood pressure. Linear regression were used to multivariate analysisResults: Seventy five percent of subjects was hypertensive with mean of blood pressure was 89,25 Â± 14,64 mmHg. The result showed that most subject (64,3%) were minimally active with mean 2.258,4Â±1.228,8 MET-minutes/week. Majority, subjects were moderate stress (56,3%). There were an association between physical activity with diastolic pressure, but not in systolic pressure. There were no association between stress with blood pressure.Conclusion: Physical activity was only associated with diastolic pressure and stress was not associated with blood pressure.